ANALISIS KEBERADAAN CELE DALAM PERSEFEKTIF KEBHINEKAAN GLOBAL - Sitti Rochmi Tatisina; Lisye Salamor; Jumiati Tuharea (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Indonesia's cultural diversity can be said to have advantages compared to other countries. This illustrates that basically it is not easy to unite diversity without a national character that has noble character and is guided by the principles of Pancasila. This research aims to determine the understanding of students, teachers and the opinions of the Education Department regarding the wearing of cele clothes in educational institutions. This author entitled "Analysis of Cele's Existence from the perspective of global diversity among students at SMP Negeri 6 Ambon and SMP Negeri 7 Ambon. This research is quantitative research with a survey approach. From the results of the research, the researcher's result is that the understanding and implementation of the policy related to diversity in the perspective of diversity in the city of Ambon among students at SMP Negeri 6 Ambon and SMP Negeri 7 Ambon obtained a large percentage figure in the "good" category, namely 59%. Teachers' understanding regarding the cela policy in the perspective of diversity in the city of Ambon at SMP Negeri 6 Ambon and SMP Negeri 7 Ambon, the result was that the teacher council had insight/knowledge about the cela which is required in the education unit. as well as the understanding/opinion of the education service regarding the cele policy from the perspective of diversity in the city of Ambon, the results have been obtained that cele clothes are required by every education unit and its staff. As a form of rule called "one day with Maluku culture". Keywords: Cele, Global Diversity